2010
DOI: 10.1073/pnas.1004100107
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide S facilitates cue-induced relapse to cocaine seeking through activation of the hypothalamic hypocretin system

Abstract: Drug addiction is a chronic relapsing disorder characterized by compulsive drug seeking and use. Environmental conditioning factors are among the major determinants of relapse in abstinent cocaine users. Here we describe a role of the neuropeptide S (NPS) system in regulating relapse. In rats with a history of cocaine selfadministration, presentation of stimuli predictive of drug availability reinstates drug seeking, triggering relapse. Intracerebroventricular (ICV) injection of NPS increased conditioned reins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
102
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 28 publications
14
102
1
Order By: Relevance
“…When administered into the LH, NPS enhances reinstatement of alcohol and cocaine seeking triggered by environmental conditioning factors. This effect is blocked by peripheral administration of the OX1 antagonist SB334867, which suggests an important interaction between these two peptidergic systems (15,16,19). In addition, NPS facilitates cocaine reinstatement with mechanisms mimicking, at least in part, the effect of stress and that may involve the corticotropin releasing factor and the Hcrt-1/Ox-A systems as well (20)(21)(22).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…When administered into the LH, NPS enhances reinstatement of alcohol and cocaine seeking triggered by environmental conditioning factors. This effect is blocked by peripheral administration of the OX1 antagonist SB334867, which suggests an important interaction between these two peptidergic systems (15,16,19). In addition, NPS facilitates cocaine reinstatement with mechanisms mimicking, at least in part, the effect of stress and that may involve the corticotropin releasing factor and the Hcrt-1/Ox-A systems as well (20)(21)(22).…”
mentioning
confidence: 87%
“…In previous studies, we demonstrated that the proreinstatement activity of Hcrt-1/Ox-A can be triggered by upstream activation of the neuropeptide S (NPS) system (14)(15)(16). NPS is a neurotransmitter produced in the pericoerulear zone of the brainstem and is released in the lateral hypothalamus (LH) where it activates its cognate G q/s protein-coupled receptor named neuropeptide S receptor (NPSR) (17,18).…”
mentioning
confidence: 99%
“…Animals were then trained to self-administer cocaine (0.125, 0.25, and 0.5 mg/0.1 ml) or heroin (20 μg/ 0.1 ml) under a fixed ratio 1 (FR1) with 20 s time-out (TO) schedule of reinforcement, in which each response at the drug-paired active lever resulted in the IV delivery of 0.1 ml of fluid, whereas responses at the inactive lever resulted in no fluid delivery (Kallupi et al, 2010). Rats received 2 h daily sessions for 13-14 consecutive days.…”
Section: Cocaine and Heroin Self-administration Under Fixed Ratio 1 Smentioning
confidence: 99%
“…Orexin peptide is known to promote wakefulness and suppresses sleep [27]. Central infusion of NPS activates orexin-containing neuron such as orexin-A [28] to facilitate dopamine neurotransmission in the nucleus accumbens [29], which might promote waking and inhibit sleep. Therefore, stimulation of NPS receptors in the lateral hypothalamic area might result in the activation of orexin-A neurons to mediate its effects through the dopamine circuits.…”
Section: Discussionmentioning
confidence: 99%